2007
DOI: 10.1111/j.1532-950x.2007.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Equine Adipose Tissue‐Derived Stromal Cells: Adipogenic and Osteogenic Capacity and Comparison with Bone Marrow‐Derived Mesenchymal Stromal Cells

Abstract: Adipose tissue is a potential source of adult stem cells for tissue engineering applications in equine veterinary medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
209
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(239 citation statements)
references
References 36 publications
23
209
1
6
Order By: Relevance
“…Vidal et al (2007) also observed that cell populations obtained from adipose tissue did not form as many colonies as cells from bone marrow, and that they were distributed more uniformly and adhered more firmly to the culture plate, as observed in this study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Vidal et al (2007) also observed that cell populations obtained from adipose tissue did not form as many colonies as cells from bone marrow, and that they were distributed more uniformly and adhered more firmly to the culture plate, as observed in this study.…”
Section: Discussionsupporting
confidence: 65%
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…For the subsequent passages, cells were inoculated in 5 cm 2 flasks at 25!10 3 cells/cm 2 and allowed to multiply for 6-7 days to 90% confluence before trypsinization and successive passage. DT and CD were calculated from haemocytometer counts and cell culture time (CT) for each passage according to the following two formulae (Vidal et al 2007):…”
Section: Cell Doubling Methodsmentioning
confidence: 99%
“…Stem cells are an interesting cellular model to study differentiation mechanisms because of the relative ease of establishing in vitro cultures and their good proliferation (Bianco et al 2001). Equine mesenchymal stem cells have been established in vitro from different tissues such as bone marrow (Fortier et al 1998), umbilical cord blood (Reed and Johnson 2008) and adipose tissue (Vidal et al 2007) and show differentiation capabilities into mesodermal lineages. Nevertheless, alternative cell sources to be used in veterinary clinical applications such as tissue engineering and repair are still necessary.…”
Section: Introductionmentioning
confidence: 99%